2023
DOI: 10.12688/f1000research.108884.2
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of syrinx morphometry and sound frequency association during the chirping period in lovebirds (Agapornis fischeri)

Abstract: Background: In the issue of biodiversity, the domestication of birds as pets and trade animals requires special attention as a conservation effort. Lovebirds (Agapornis fischeri) are popular birds worldwide, due to their varied ornamentation and melodic chirping sound. Syrinx structure is suspected to be the main source of sound production during the chirping period. This study aimed to investigate syrinx morphometry and its correlation with sound frequency produced in lovebirds. Methods: A total of 24 lovebir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 43 publications
2
3
0
Order By: Relevance
“…The superficial and deep syringeal muscles are examples of intrinsic muscles and, in this study, they were found only in the white‐eyed parakeet, similar to what was described for other parrots (Dewi et al, 2023; Gaunt & Gaunt, 1985). According to Casteleyn et al (2018), the most domestic bird species had no intrinsic syringeal muscles.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…The superficial and deep syringeal muscles are examples of intrinsic muscles and, in this study, they were found only in the white‐eyed parakeet, similar to what was described for other parrots (Dewi et al, 2023; Gaunt & Gaunt, 1985). According to Casteleyn et al (2018), the most domestic bird species had no intrinsic syringeal muscles.…”
Section: Discussionsupporting
confidence: 87%
“…In this study, the pessulus was observed in red‐legged seriema and red‐winged tinamou. No pessulus is present in the white‐eyed parakeet, similarly to reported for other Psittacidae family birds such as monk parakeet and Patagonian parrot (Dyce et al, 2010; Gaunt & Gaunt, 1985) and loverbirds (Dewi et al, 2023). The composition of pessulus, dividing the airway within the syrinx, varies significantly in the avian species (Frank et al, 2006).…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations